Learning interspecific communicative responses in Pampas foxes (Lycalopex gymnocercus) - Barrera, Gabriela Luciana (2012)
Domestic dogs show remarkable communicative abilities in their interaction with people. These skills maybe explained by the interaction between the domestication process and learning experiences during ontogeny. Studies carried out on other species of canids, which have not been domesticated are relevant to this topic. The purpose of this article is to study the effect of instrumental learning on captive Pampas foxes' (Lycalopex gymnocercus) communicative responses to humans. Seven foxes were tested in a conflict situation involving food within sight but out of their reach. In these situations dogs typically gaze at the human face to ask for food. In Study 1, there was an increase in gaze duration as a consequence of reinforcement and a decrease during extinction, when animals did not receive any more food. In Study 2, all of the four foxes tested successfully followed proximal pointing gesture to find hidden food. When a distal pointing cue was given, three out of four followed it in the first session and one in the second session. These results are consistent with those previously found in dogs, and suggest that learning experiences allow the development of communicative skills, even in not domesticated canid species.